1997
DOI: 10.3109/00016489709117777
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Drugs in the Treatment of Cochlear Disorders: A Clinical and Experimental Study

Abstract: On the grounds of positive results obtained with Meniere's patients, agents such as glycerol and mannitol have been included in the therapeutical protocol of other cochlear disorders presenting with hearing loss either of sudden onset, but not observed at an early stage, or accompanied by tinnitus and aural pressure. Intravenous infusions of either 10% glycerol or 18% mannitol were given to selected patients 3 to 6 times with a time interval of 1 to 3 days. Hearing loss, tinnitus and aural pressure were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Gene alterations at these loci restate reported cytogenetic [7, 1222] and molecularly altered regions by LOH and array CGH studies in HNSCC [1, 5, 7, 2328]. Additionally, copy number loss in tumor and corresponding gain in nontumor, and vice versa, advocate aneuploidy events.…”
Section: Resultsmentioning
confidence: 56%
“…Gene alterations at these loci restate reported cytogenetic [7, 1222] and molecularly altered regions by LOH and array CGH studies in HNSCC [1, 5, 7, 2328]. Additionally, copy number loss in tumor and corresponding gain in nontumor, and vice versa, advocate aneuploidy events.…”
Section: Resultsmentioning
confidence: 56%
“…In clinical trials, dehydration agents (e.g., mannitol, isosorbide, and glycerol) are commonly used in the diagnosis and treatment of MD ( Kakigi et al, 2004 ), as their influences on hearing improvement have been confirmed by clinical trials and research ( Filipo et al, 1997 ; Degerman et al, 2019 ). The impacts of dehydration agents in animal models have usually been analyzed by tissue section or micro-CT.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an open trial tinnitus was only relieved in 13.1% of patients treated with glycerol and 5.8% of those treated with mannitol (160). …”
Section: Existing Treatmentsmentioning
confidence: 99%